Functional expression and properties of a nicotinic alpha9/5-HT3A chimeric receptor - Verbitsky, Miguel (2003)
We describe the functional properties of a nicotinic alpha9/serotonin subtype 3A (5HT3A) chimeric receptor expressed in Xenopus laevis oocytes. The chimera preserved ligand-binding properties of alpha9 and channel properties of 5HT3A. Thus, it responded to acetylcholine in a concentration-dependent manner with an EC50 of 70 microM but not to serotonin. It was blocked by methyllycaconitine, strychnine, atropine and nicotine, with the same rank order of potency as alpha9 receptors. The current-voltage relationship of currents through the alpha9/5HT3A chimera was similar to that of the 5HT3A receptors. These results are an evidence of functional coupling between the ligand-binding and the channel domains of the chimeric receptor.